Antibacterial activity of calcium hydroxide combined with triple antibiotic paste against enterococcus faecalis; an ın vitro study - Adem Kuşgöz; Erhan Özcan; İpek Arslan; Melek İnci (Cumhuriyet University, 2013)
Objectives: The aim of the present in vitro study was to investigate the antibacterial efficacy of calcium hydroxide mixed with triple antibiotic paste at various rates. Materials and Methods: Triple antibiotic paste (TAP; metronidizol, minocycline, ciprofloxacin) and calcium hydroxide powder was mixed in different proportions and tested for antibacterial activity against E. faecalis (ATCC 29212)using the agar diffusion method. The samples were divided into 10 different groups;Group 1: 100% Ca(OH)2, Group 2: 99,5% Ca(OH)2 + 0.5% TAP, Group 3: 99% Ca(OH)2 + 1%TAP,  Group 4: 97,5% Ca(OH)2 + 2,5% TAP, Group 5: 95% Ca(OH)2 + 5%TAP, Group 6: 90% Ca(OH)2 + 10%TAP,  Group 7: 75% Ca(OH)2 + 25% TAP, Group 8: 50% Ca(OH)2 + 50% TAP, Group 9: 25% Ca(OH)2 +  75% TAP, Group 10: %100 TAP. Standard holes in the cultivated agar plates were filled with one of the samples and the zones of microbial inhibition were measured after incubation period (48 hours). The experiment was performed 8 times with each medicament. Results: Group 1 had no effect against E.faecalis. Group 10 demonstrated high antibacterial activity than any other groups in this study. The antibacterial effects of the groups could be ranked from strongest to weakest as follows: Group 10, 9, 8, 7, 6, 5, 4, 3, 2, 1. Conclusions: Adding the triple antibiotic paste increased he antibacterial efficacy of calcium hydroxide. In addition, the antibacterial effect of calcium hydroxide also increased with higher proportion of TAP.